2000
DOI: 10.1002/1521-396x(200006)179:2<387::aid-pssa387>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

On the Photoacoustic Characterization of Semiconductors: Influence of Carrier Recombination on the Thermodiffusion, Thermoelastic and Electronic Strain Signal Generation Mechanisms

Abstract: A quantitative study of the photoacoustic (PA) signal dependence on the modulation frequency in semiconductors was performed. The carrier recombination processes were taken into account to calculate the PA signal, considering the thermodiffusion (TD), thermoelastic (TE) and electronic strain (ES) signal generation mechanisms. Analytical expressions for these contributions and for the total pressure in the PA gas chamber are given for the heat transmission detection configuration. The theoretical results were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The experimental set-up is standardized using a silicon wafer of thickness 420 µm and indium phosphide of thickness 350 µm. We obtained thermal diffusivity values of 0.93 ± 0.007 cm 2 s −1 for silicon wafer and 0.42 ± 0.002 cm 2 s −1 for indium phosphide, which are in accordance with the literature values [22,23]. The samples, in the form of discs of diameter 1 cm are fixed on to the cell using vacuum grease.…”
Section: Methodology and Resultssupporting
confidence: 89%
“…The experimental set-up is standardized using a silicon wafer of thickness 420 µm and indium phosphide of thickness 350 µm. We obtained thermal diffusivity values of 0.93 ± 0.007 cm 2 s −1 for silicon wafer and 0.42 ± 0.002 cm 2 s −1 for indium phosphide, which are in accordance with the literature values [22,23]. The samples, in the form of discs of diameter 1 cm are fixed on to the cell using vacuum grease.…”
Section: Methodology and Resultssupporting
confidence: 89%
“…[7][8][9][10][11][12][13] In photoacoustics (PA), for instance, some theoretical studies showed that the number of photogenerated excess carriers generated in both n-and p-type semiconductors illuminated with a modulated light source increases with the light absorption, and they are able to significantly change the temperature distribution at the surface and inside the materials. [14][15][16][17][18] The experimental observation of these effects still remains a challenge due to the separate analysis of either the amplitude or phase of the PA signal in a relatively short range of modulation frequencies. [19][20][21][22][23] The simultaneous monitoring of both of these signals in a wide interval of modulation frequencies is thus desirable to observe the effects of photogenerated excess carriers.…”
Section: Introductionmentioning
confidence: 99%